Effect of Magnetic Field From Mobile Phone on Brain - Ali, Esmail Abdo Mohammed (CIRWORLD, 2015)
Human exposure to electromagnetic field (EMF) comes from many different sources and occurs in various situations in everyday life. Man-made static fields are mainly found in occupational settings, such as close to magnetic resonance imaging (MRI) scanners, although DC high-voltage overhead transmission lines are being constructed, which are expected to expose larger parts of the population to static electric and magnetic fields.Today, for power regulation most modern electrical equipment uses electronics instead of transformers. Examples include the switched power supplies to laptops, drilling tools, chargers of mobile phones and similar devices. As a consequence, the frequency content of the daily magnetic field exposure has changed mainly by adding odd harmonics (150 Hz, 250 Hz, 750 Hz, etc.). In particular, the third harmonic (150 Hz) has become another dominating frequency in our environment.In particular for brain tissues, the mobile phone used at the ear remains the main source of exposure. However, since the first generation of mobile telephony, the technology aimed at reducing the emitted power of mobile handsets. In particular, for Global System for Mobile communication (GSM) already the introduction of dynamic power control reduced the average output power to about 50% of its rated value during calls, whereas the use of discontinuous transmission during voice calls gave a further 30% reduction in average emitted power. Adaptive power control became faster and more effective in the third-generation (3G) of mobile telephony systems leading to a further reduction (by about two orders of magnitude) in the specific absorption Specific energy Absorption Rate (SAR) compared to GSM phones. In addition, hands-free kits reduce the energy absorbed by the head drastically. Digital Enhanced Cordless Telecommunications (DECT) phones are another source of everyday exposure.